Genetic Polymorphisms Associated with Cyclophosphamide Outcome and Risk of Toxicity in Patients with Lupus Nephritis - Yen Yen Ari Indrawijaya; Laniyati Hamijoyo; Aluicia Anita Artarini; Maria Immaculata Iwo (Acta Medica Indonesiana, 2023)
A 6-month cyclophosphamide induction therapy followed by maintenance therapy every three months is the first-line treatment for Class III, IV, and V lupus nephritis. Among the 139 single nucleotide polymorphisms (SNPs) associated with cyclophosphamide, four SNPs, namely rs4244285, rs4802101, rs7254579 and rs3957356, are related to the response and risk of toxicity in patients with lupus nephritis. Although pharmacogenetic studies in patients with lupus nephritis (LN) have not been conducted previously in Indonesia, data on rs4244285 are available for several ethnic groups, including Papuans, Bataks, Balinese, Dayaks, Javanese, Bugis, Chinese, Timorese and Malays, even though direct evidence in LN patients is less detectable. However, this can be followed up prior to cyclophosphamide therapy based on the identification of genetic markers. Therefore, clinical studies in patients with lupus nephritis are deemed necessary to evaluate the potential of these markers.